(untitled) (Malaysian Journal of Learning and Instruction, 2023)
Purpose – The present study explores a tricomponent attitude model for “forced” online learning applied in the post-Covid era following the online learning transition. The study aims to provide a reference for future practitioners in the event a similar crisis results in the mandatory transition towards this study mode again. Methodology – Following the guideline for judgmental sampling, a total of 156 valid responses were collected from Malaysian undergraduate students via an online questionnaire from Google Forms. The respondents’ profiles were computed using the Statistical Package for the Social Sciences (SPSS) version 21.0, while Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to validate the measurement model, structural model, and mediation model for hypothesis testing. Findings – The findings demonstrate that perceived usefulness (PU) is insignificant when online learning is the only feasible learning strategy. Technical system quality (TSQ) was found to be positively related to perceived ease of use (PEU), attitude (ATT), and student satisfaction, while quality of content (QC) was found to be positively related to PEU and student satisfaction. The remaining hypotheses were rejected. These findings are expected to transform various student attitude, leading to the cognitive components of PEU and PU and ultimately contributing to student satisfaction. In line with the government’s desire to transform digital education in higher education, TSQ and QC constitute a framework for shaping the affective components of students’ attitude. Attitude, in turn, drives students’ PEU and PU, which are two critical factors of the Technology Acceptance Model that serve as the main determinants of student satisfaction. Significance – The study demonstrates that instructors can use a variety of strategies to increase student satisfaction with online education, which can be beneficial even in the post-Covid era. The findings can aid education providers in implementing necessary changes to improve online learning for their students in the future. In addition, the study reveals that through the pandemic, students have become more resilient and have begun to value online learning, highlighting the importance of considering the long-term effects of online learning on student satisfaction.